التقدير القياسي لبعض أهم العوامل المؤثرة على الإنتاج الزراعي في ليبيا وتقدير حجم الإنتاج الأمثل لأهم المحاصيل المنتجة في القطاع الزراعي في ليبيا خلال الفترة ما بين 1990 إلى 2010 - نور الدين محمد عبد النبي (Scientific Journal of University of Benghazi, 2021)
The Libyan agricultural sector plays important role providing food and employment to residential population. Libya, as one of the oil-producing countries, and compared to other oil-producing countries, did not reflect this prosperity on the required standard of living. Also, working to develop the agricultural production sector has become a very urgent necessity in a country that imports more than 80% of its food needs from abroad. The paper aimed to identify the most important factors that affect agricultural production in Libya, which may have negative effects on agricultural production, which is one of the reasons that can impede sustainable economic development, as the average percentage of the contribution of the value of agricultural production to the gross domestic product is low in recent years, about 31% during the period from 1990 to 2010. The study relied on the method of quantitative economic analysis and the optimum level of production from some of the most important crops in Libya was estimated according to Nerlov's partial adjustment model. The increasing growth rates for the total number of total employment, the total population (in million people), the cultivated area, the total number of agricultural tractors, and the total amount of chemical fertilizers reached about 24%, 3.2%, 1.9%, 22.4% and 14.1%, respectively. While the growth rates were declining for the number of agricultural labor, the area of crops, and the total number of animal units, reaching about 5.6%, 6.1% and 0.3% respectively. It was found that the volume of optimum production in light of the available economic resources can be increased in wheat, barley, maize crops, legumes group, vegetables group, fruit group in quantities of about 101.2, 660.1, 0.3, 529.0, 882.7, 291.9 thousand tons and can reduce The size of the food gap of these crops.